How the innovative advertising language style for nutrition products affects consumers' purchase intentions - Lu, Geng; Cao, Jun; Wei, Yunyun; Yang, Dajun; Tan, Fuqiang (Frontiers in Nutrition, 2025)
ObjectiveIn the competitive market for nutrition products, advertising strategies play a pivotal role in shaping consumer behavior. This study investigated how advertising language styles (disruptive vs. sustaining) influence consumer purchase intentions for nutrition products, examining information processing fluency as a mediator and information credibility as a moderator.MethodsA multi-group experiment was conducted with 852 participants, recruited via a professional survey platform, in a controlled simulated environment. Data on participants' gender, exposure to advertising language styles (disruptive vs. sustaining), purchase intentions, information processing fluency, and information credibility (high vs. low) were collected using an online questionnaire. PROCESS models (Model 4 for mediation, Model 1 for moderation) and ANOVA (for main effects) were used for statistical analysis.ResultsDisruptive advertising language, compared to sustaining styles, significantly enhanced consumers' attention, interest in product innovations, and purchase intentions. Information processing fluency mediated the positive relationship between advertising language style and purchase intention, highlighting the importance of clarity and ease of understanding.ConclusionsDisruptive advertising language, fluent information processing, and high information credibility are key factors in enhancing consumers' purchase intentions for nutrition products.